Transfer Function Models for the Localization of Seizure Onset Zone From Cortico-Cortical Evoked Potentials - Kamali, Golnoosh; Smith, Rachel June; Hays, Mark; Coogan, Christopher; Crone, Nathan E.; Kang, Joon Y.; Sarma, Sridevi V. (Frontiers in Neurology, 2020)
Surgical resection of the seizure onset zone (SOZ) could potentially lead to seizure-freedom in medically refractory epilepsy patients. However, localizing the SOZ can be a time consuming and tedious process involving visual inspection of intracranial electroencephalographic (iEEG) recordings captured during passive patient monitoring. Single pulse electrical stimulation (SPES) is currently performed on patients undergoing invasive EEG monitoring for the main purposes of mapping functional brain networks such as language and motor networks. We hypothesized that evoked responses from SPES can also be used to localize the SOZ as they may express the natural frequencies and connectivity of the iEEG network. To test our hypothesis, we constructed patient specific transfer function models from the evoked responses recorded from 22 epilepsy patients that underwent SPES evaluation and iEEG monitoring. We then computed the frequency and connectivity dependent “gain” of the system as measured by the H_∞ norm from systems theory. We found that in cases for which clinicians had high confidence in localizing the SOZ, the highest gain transfer functions with the smallest input norms corresponded to when the clinically annotated SOZ and early spread regions were stimulated. In more complex cases, there was a large spread of the system gains when the clinically annotated SOZ was stimulated. Interestingly for patients who had successful surgeries, our ratio of system gain-to-input norm, the GN ratio, agreed with clinical localization, no matter the complexity of the case. For patients with failed surgeries, the system GN gain ratio did not match clinical annotations. Our findings suggest that transfer function gains and their corresponding input norms computed from SPES evoked responses may improve SOZ localization and thus surgical outcomes.